“Teaching Physics with Interdisciplinary Project Based Teaching and Learning (IPBTL) Model” - Sharma, Dipti (European Journal of Applied Sciences, 2021)
Teaching Physics to Physics minors or non-Physics major is always challenging. In this article, an example of teaching Physics to working students using interdisciplinary project is shown. In other words, a teaching model called Interdisciplinary Project Based Teaching and Learning (IPBTL) is introduced with results found in class. The results showed that the model brought significant increase in students’ interest of learning and understanding the depth of Physics and made them capable to connect knowledge of Physics with real world applications. As an example, the project ran in one semester of the Physics course called as “Applying Ohm’s Law to the real world monetary coins i.e. Penny, Nickel, Dime and Quarter” is shown. This project was given to students who were learning the concept of electricity, and they work in the area of electricity.